ANALISIS POTENSI LIKUIFAKSI DI DAERAH SERANGAN BALI SELATAN MENGGUNAKAN METODE PROBABILISTIK DAN METODE GROUND PENETRATING RADAR (GPR) - Putri, Maya Efiarni Eka; Siregar, Rahmat Nawi; Singarimbun, Alamta (Jurnal Riset Fisika Indonesia, 2021)
Liquefaction causes physical damage on land and has potential to cause more fatalities. In addition, southern part of Bali Island is one of the tourist destination areas with quite high liquefaction potential due to soil condition and large number of potential earthquakes. Research on liquefaction potential analysis at Serangan, Southern Bali was conducted by using probabilistic and ground penetrating radar (GPR) methods. This research aims to obtain information on shallow layers, land subsidence dueto earthquakes theoretically, and probability of liquefaction occurrences in the area of Serangan, Southern Bali by considering several parameters, such as Bali earthquake (2020) and Lombok earthquake (2018). The GPR data was processed by ReflexW 7.0 software, and probabilistic by Microsoft Excel 2010. The probabilistic and GPR results indicated ground water level was at 2 m depth and the liquefaction occurrence was 92.22% with ground acceleration of 0.5749 gal at 3.5 m in depth, which was 10 km away from epicenter due to an earthquake with a magnitude of 7.7. Keywords: Ground Water Level; Land Subsidence; Probability; ReflexW 7.0 Software